Globular C1q Receptor (gC1qR/p32/HABP1) Suppresses the Tumor-Inhibiting Role of C1q and Promotes Tumor Proliferation in 1q21-Amplified Multiple Myeloma - Xu, Jiadai; Sun, Yifeng; Jiang, Jifeng; Xu, Zhao; Li, Jing; Xu, Tianhong; Liu, Peng (Frontiers in Immunology, 2020)
Immunodeficiencies are widely becoming known as important features of multiple myeloma (MM) and may promote the proliferation of malignant cells as well as confer resistance to therapy. Few studies focus on the immunomodulatory effects of the complement system on MM. This study aims to explore the role of C1q in MM patients. Plasma C1q was found to be significantly reduced in MM patients, and the amount of C1q deposited around the CD138+ cells in BM biopsy sections was observed to be much higher, especially in the subgroup with 1q21 amplification (Amp1q21). CD138+ cells expressed higher levels of C1q receptors (C1qRs) than CD138- cells. Patients with Amp1q21 expressed higher levels of globular C1q receptor (gC1qR), while patients without Amp21 expressed higher levels of collagen tail C1q receptor (cC1qR). Additionally, gC1qR was noted to suppress the MM-inhibiting role of C1q in H929, U266 and MM1S. gC1qR interacts with insulin-like growth factor 2 mRNA binding protein 3 (IGF2BP3), which also suppressed the function of C1q and regulated CDC28 protein kinase regulatory subunit 1B (CKS1B) mRNA. In summary, gC1qR suppressed the MM-inhibiting role of C1q and regulated CKS1B mRNA in promoting tumor proliferation via IGF2BP3 in 1q21-amplified MM. Our findings provide novel evidence on how MM cells evade the immune system and promote survival as well as suggest possible novel targets for future therapies of MM.